2013
DOI: 10.1186/1476-069x-12-55
|View full text |Cite
|
Sign up to set email alerts
|

A time series study on the effects of heat on mortality and evaluation of heterogeneity into European and Eastern-Southern Mediterranean cities: results of EU CIRCE project

Abstract: BackgroundThe Mediterranean region is particularly vulnerable to the effect of summer temperature.Within the CIRCE project this time-series study aims to quantify for the first time the effect of summer temperature in Eastern-Southern Mediterranean cities and compared it with European cities around the Mediterranean basin, evaluating city characteristics that explain between-city heterogeneity.MethodsThe city-specific effect of maximum apparent temperature (Tappmax) was assessed by Generalized Estimation Equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 27 publications
(62 reference statements)
6
47
0
Order By: Relevance
“…A greater increase in mortality on heatwave days was observed in Mediterranean cities compared with cities in northern parts of Europe (21.8% and 12.4% mortality increase, respectively) [15]. In contrast, cities with cooler climates have a greater increase in mortality per 1 °C increase above a local temperature threshold, compared to warmer cities [18]. A study in Central Italy found that a 1 °C increase in temperature above a threshold was associated with an increase in mortality of up to 15.97% among people aged 75 years or more, over a lag period of 30 days [19].…”
Section: High Temperature and Heatwavesmentioning
confidence: 89%
See 2 more Smart Citations
“…A greater increase in mortality on heatwave days was observed in Mediterranean cities compared with cities in northern parts of Europe (21.8% and 12.4% mortality increase, respectively) [15]. In contrast, cities with cooler climates have a greater increase in mortality per 1 °C increase above a local temperature threshold, compared to warmer cities [18]. A study in Central Italy found that a 1 °C increase in temperature above a threshold was associated with an increase in mortality of up to 15.97% among people aged 75 years or more, over a lag period of 30 days [19].…”
Section: High Temperature and Heatwavesmentioning
confidence: 89%
“…However, temperature-dependent mortality is also high among young populations, particularly in Eastern and Southern Mediterranean cities including Istanbul and Tel Aviv [18]. Increased summer temperatures also have consequences for pregnancy and preterm birth.…”
Section: High Temperature and Heatwavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the impact of thermal extremes on mortality has been analysed from two different standpoints. While some studies have targeted the effects had by heat on morbidity and mortality (Leone et al 2013;Baccini et al 2013;Montero et al 2012;D'Ippoliti et al 2010;Basu 2009;Linares and Díaz 2008;Kovats and Ebi 2006;Díaz et al 2002), others -albeit less numerous-have targeted the effects had by cold waves on health (Montero et al 2010a;Díaz et al 2005;Donaldson and Rintamäki 2001;The Eurowinter Group 1997). However, few studies have compared the differentiated behaviour patterns of the respective extremes on mortality in a given population in the same region over the same period of time (Zanobetti et al 2013;Hajat et al 2007;Medina-Ramón et al 2006;Braga et al 2002;Huynen et al 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have shown that temperature is one of the main climatic factors that influence mortality (Anderson & Bell, 2009;Basu, 2009;D'Ippoliti et al, 2010;Guirguis, Gershunov, Tardy, & Basu, 2014;Hajat & Kosatky, 2010;Leone et al, 2013); therefore, ManneKendall tests (Kendall, 1975;Mann, 1945) were applied to the temperature series of Lisbon's meteorological station (IDL, 1856e2012, Table 2, Fig. 1) in order to determine the presence of a trend (Rau, 2007;Sousa, García-Barr on, & Jurado, 2007).…”
Section: Climatic Time Patternsmentioning
confidence: 99%